Determinación del ciclo de vida del gusano cogollero (Spodoptera frugiperda), y el barrenador del tallo (Diatraea saccharalis), de maíz en condiciones controladas. - Moreira Cedeño, Luis Eduardo (2020)
Maize (Zea mays L.) is a crop of great importance in the country, it is widely used in the human and animal diet. Although the management of the maize crop is well known, the presence and management of its pests continue to represent one of the most serious problems for the producer. Among the main insect pests of economic importance, we find the armyworm (Spodoptera frugiperda) and the stem borer (Diatraea saccharalis). Information about the biological cycle of these two insect-pest species is necessary to establish integrated management plans for these pests. The following research aims to determine the life cycle of the armyworm (S. frugiperda) and the stem borer (D. saccharalis) in the maize crop under controlled conditions. This research was carried out at the Universidad Técnica Estatal de Quevedo in the Microbiology Laboratory. Stem borer and armyworm larvae were raised and fed with natural diet and multiplied to determine the biological cycle of each species. The biological cycle of S. frugiperda was 47 days (from egg to adult stage), females on average oviposited 753 eggs, with a fertility percentage of 82%. The larval stage of S. frugiperda was 22 days; of the pupa, 11 days, and the average longevity of adults was of 11 days. In the case of D. saccharalis, the biological cycle was 44 days, the mean number of eggs oviposited by females was 173 eggs, with a fertility percentage of 74%. The larva stage was 27 days, pupa, 10 days; and the average longevity of adults was 4 days. In the two species evaluated, the morphometric parameters of each stage of the biological cycle were evidenced. The results obtained allow updating the information of these two species to establish programs that permit the timely control of these pests. Key Words: Morphometry, reproduction, maize, metamorphosis